Letter: proton pump inhibitor use and risk of fracture. Issue 11 (17th May 2018) - Zhao, J.; Wang, J. M.; Zhang, X. W.; An, R.; Liang, C.
Abstract : Linked Content This article is linked to Torvinen‐Kiiskinen et al paper. To view this article visithttps://doi.org/10.1111/apt.14589 .